2011
DOI: 10.1007/s11669-010-9846-x
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Section of the Nb-Si-B System at 1700 °C in the Nb-NbSi2-NbB2 Region

Abstract: Me-Si-B (Me-metal) alloy systems have been evaluated to aid the development of ultra high temperature structural materials. In the present work, the phase relations at 1700°C in the Nb-NbSi 2 -NbB 2 region of the Nb-Si-B system have been experimentally determined. The alloys were prepared via arc melting and powder metallurgy routes. All samples were characterized via scanning electron microscopy (SEM) and x-ray diffraction (XRD) and selected samples were also scanned via wave-length dispersive spectroscopy (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Therefore the structure can be considered as a partially filled Mn 5 Si 3 -type as was first reported by Nowotny et al [6] Table 1(a) and (b)). Furthermore, the refined composition is very close to the point composition shown in the isothermal section by Nunes et al [10] at 1700 1C and lies inside the homogeneity region presented by Nowotny et al [6] at 1600 1C. No B content was found for the 6d site occupied by Si (Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore the structure can be considered as a partially filled Mn 5 Si 3 -type as was first reported by Nowotny et al [6] Table 1(a) and (b)). Furthermore, the refined composition is very close to the point composition shown in the isothermal section by Nunes et al [10] at 1700 1C and lies inside the homogeneity region presented by Nowotny et al [6] at 1600 1C. No B content was found for the 6d site occupied by Si (Fig.…”
Section: Resultssupporting
confidence: 84%
“…2, Table 1(a) and (b)) and unambiguously showed that B shares the 8h site with Si (0.89Bþ0.11Si) revealing a composition Nb 62.5 Si 15.3 B 22.2 (at %). This composition is slightly lower than the maximum amount of B in this phase (25%) [9,10] and it seems that Si will entirely be replaced by B at the limit of the solid solution. It must be noted that no B was found in the 4a site (Si1) and thus the boron site preference in this phase is similar to the isotypic solid solution Ta 5 (Si 1 À x B x ) 3 , (x ¼0.568(3)) in the Ta-Si-B system.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The lattice parameters of Nb SS in the hotpressed Nb-4Si-8B and Nb-8Si-16B alloys were varied from a=3.3030Å to a=3.2961Å. According to the phase diagram of the Nb-Si-B system, the microstructures of the heat-treated Nb-4Si-8B and Nb-8Si16B alloys are basically formed by the Nb SS and Nb 5 SiB 2 (T2-phase) [5]. In addition, some reflections of Nb 3 B 2 were identified in XRD pattern of the hot-pressed Nb-4Si-8B and Nb-8Si-16B alloys.…”
Section: Nbmentioning
confidence: 99%
“…In ternary Nb-Si-B alloys, T2-phase with stoichiometric ratio close to Nb 5 SiB 2 can dissolve a large amount of boron of up to 25 at-% B. Depending on alloy composition, other Nb 5 Si 3 -phase with D88 structure can be formed during solidification and subsequent heat treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%